Refinement of primary carbides in AISI DC 53 cold work tool steel by thin section copper permanent mould casting and water atomization. (4th May 2019) - Çardaklı, Ismail Seçkin; Kalkanlı, Ali
ABSTRACT: In this study, as alternative methods to conventional production methods involving thin section copper permanent mould casting (fast solidification) and water atomization (rapid solidification) of AISI DC 53 cold work tool steel have been investigated. Thin slabs obtained by copper mould casting was homogenized at 1150 °C for one hour and then hot rolling was be applied. After hot rolling, conventional heat treatment have been applied to thin slabs. The same heat treatment procedure have been performed for a commercially available AISI DC 53 which is manufactured by thick section ingot casting and rolling. In order to investigate also the effect of rapid solidification on AISI DC 53 tool steel, steel powder was produced by water atomization technique. Experiments have revealed that thin steel slabs in permanent copper mould and rapidly solidified tool steel powder by water atomization have a more refined primary M7 C3 carbides than commercially available steel.